Quantitative Detection of the Partially Purified Endotoxin Extracted from the Locally Isolated Salmonella typhimurium A3 - Al-Saffar, Ali Z; Ahmed, Salman A; Hussein, Shalal M (Al-Nahrain Journal of Science, 2011)
A total of 95 stool samples were collected from pediatric patients suffering from diarrhea in order to isolate bacteria belonging to Salmonella typhimurium species. After performing microscopic examination, cultural characterization, biochemical and Api 20E identifications, only 9 isolates showed positive Salmonella typhimurium. Following the separation of endotoxin from each isolate the biological activity of endotoxin was estimated by using E-TOXATE kit (Limulus amebocyte lysate test) and the isolate Salmonella typhimurium A3 showed the lowest concentration that gave positive result (0.5 µg/ml). Partial purification of endotoxin using sepharose Cl-6B gel chromatography for A3 endotoxin was applied and after purification two peaks were obtained. Chemical characterization involving the estimation of carbohydrate and protein contents showed that the first peak contained the higher carbohydrate contents (38.6%) and lower protein contents (1.15%) as compared with the second peak which showed carbohydrate and protein contents 13.2 and 5.75% respectively. In addition, the first peak showed maximum activity of (≥0.1µg/ml), the second peak and the crude endotoxin showed 2.5 and 0.5µg/ml respectively.